Adapalene Inhibits Prostate Cancer Cell Proliferation In Vitro and In Vivo by Inducing DNA Damage, S-phase Cell Cycle Arrest, and Apoptosis - Nong, Hai-bin; Zhang, Ya-nan; Bai, Yi-guang; Zhang, Qiong; Liu, Ming-fu; Zhou, Quan; Shi, Zhuo-hua; Zeng, Gao-feng; Zong, Shao-Hui (Frontiers in Pharmacology, 2022)
Aims: Prostate cancer is a well-known aggressive malignant tumor in men with a high metastasis rate and poor prognosis. Adapalene (ADA) is a third-generation synthetic retinoid with anticancer properties. We investigated the anti-tumor activity and molecular mechanisms of ADA in the RM-1 prostate cancer cell line in vivo and in vitro. Methods: The effects of ADA on cell proliferation were estimated using the CCK-8 and colony formation assays. The wound-healing assay and the Transwell assay were employed to examine the migratory capacity and invasiveness of the cells. Flow cytometry was utilized to evaluate the cell cycle and apoptosis, and Western blotting analysis was used to assess the expression of the associated proteins. Micro-CT, histomorphological, and immunohistochemical staining were used to assess the effects of ADA on bone tissue structure and tumor growth in a mouse model of prostate cancer bone metastasis. Result: ADA dramatically inhibited cell proliferation, migration, invasiveness, and induced S-phase arrest and apoptosis. ADA also regulated the expression of S-phase associated proteins and elevated the levels of DNA damage markers, p53, and p21 after ADA treatment, suggesting that the anti-tumor effect of ADA manifests through the DNA damage/p53 pathway. Furthermore, we observed that ADA could effectively inhibited tumor growth and bone destruction in mice. Conclusion: ADA inhibited prostate cancer cell proliferation, elicited apoptosis, and arrested the cell cycle in the S-phase. ADA also slowed the rate of tumor growth and bone destruction in vitro. Overall, our results suggest that ADA may be a potential treatment against prostate cancer.